Lagrangian analysis of microphysical and chemical processes in the Antarctic stratosphere: a case study - Di Liberto, L.; Lehmann, R; Arnone, E.; Dinelli, B. M.; Cairo, F.; Tritscher, I.; Fierli, F.; Mercer, J. L.; Snels, M.; Di Donfrancesco, G.; Deshler, T.; Luo, B. P.; et al. (EGU, 2014)
We investigated chemical and microphysical processes in the late winter in the Antarctic lower stratosphere, after the first chlorine activation and initial ozone depletion. We focused on a time interval when both further chlorine activation and ozone loss, but also chlorine deactivation, occur.We performed a comprehensive Lagrangian analysis to simulate the evolution of an airmass along a ten-day trajectory, coupling a detailed microphysical box model with a chemistry model. Model results have been compared with in-situ and remote sensing measurements of particles and ozone at the start and end points of the trajectory, and satellite measurements of key chemical species and clouds along it.Different model runs have been performed to understand the relative role of solid and liquid Polar Stratospheric Cloud (PSC) particles for the heterogeneous chemistry, and for the denitrification caused by particle sedimentation. According to model results, under the conditions investigated, ozone depletion is not affected significantly by the presence of Nitric Acid Trihydrate (NAT) particles, as the observed depletion rate can equally well be reproduced by heterogeneous chemistry on cold liquid aerosol, with a surface area density close to background values.Under the conditions investigated, the impact of denitrification is important for the abundances of chlorine reservoirs after PSC evaporation, thus stressing the need of using appropriate microphysical models in the simulation of chlorine deactivation. Conversely, we found that the effect of particle sedimentation and denitrification on the amount of ozone depletion is rather small in the case investigated. In the first part of the analysed period, when a PSC was present in the airmass, sedimentation led to smaller available particle surface area and less chlorine activation, and thus less ozone depletion. After the PSC evaporation, in the last three days of the simulation, denitrification increases ozone loss by hampering chlorine deactivation.